Duterte as misogynist fascist a discourse analysis of Duterte’s misogynist criticisms against women - Lanuza, Gerardo M. (2022)
Access online through this link: https://www.plarideljournal.org/article/duterte-as-misogynist-fascist-a-discourse-analysis-of-dutertes-misogynist-criticisms-against-women
Keywords: Duterte, Rodrigo Roa, 1945-; Misogyny; Discourse analysis; Violence against women